2015
DOI: 10.1007/s11745-015-4071-3
|View full text |Cite
|
Sign up to set email alerts
|

9‐Oxo‐10(E),12(Z),15(Z)‐Octadecatrienoic Acid Activates Peroxisome Proliferator‐Activated Receptor α in Hepatocytes

Abstract: The peroxisome proliferator-activated receptor (PPAR)α is mainly expressed in the liver and plays an important role in the regulation of lipid metabolism. It has been reported that PPARα activation enhances fatty acid oxidation and reduces fat storage. Therefore, PPARα agonists are used to treat dyslipidemia. In the present study, we found that 9-oxo-10(E),12(Z),15(Z)-octadecatrienoic acid (9-oxo-OTA), which is a α-linolenic acid (ALA) derivative, is present in tomato (Solanum lycopersicum) extract. We showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Therefore, KOT supplementation could significantly mitigate the increased liver TC and TG content induced by the HCD hyperlipidemia model. One recent study demonstrated that 9-oxo-10(E),12(Z),15(Z)-octadecatrienoic acid in tomato extract promotes fatty acid metabolism via PPARα activation in liver cells and has potential for use in the management of dyslipidemia [ 42 ]. In addition, 13-oxo-9(Z),11(E),15(Z)-octadecatrienoic acid in the extract of tomato induced PPARγ expression in adipose tissue and resulted in the regulation of adipogenesis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, KOT supplementation could significantly mitigate the increased liver TC and TG content induced by the HCD hyperlipidemia model. One recent study demonstrated that 9-oxo-10(E),12(Z),15(Z)-octadecatrienoic acid in tomato extract promotes fatty acid metabolism via PPARα activation in liver cells and has potential for use in the management of dyslipidemia [ 42 ]. In addition, 13-oxo-9(Z),11(E),15(Z)-octadecatrienoic acid in the extract of tomato induced PPARγ expression in adipose tissue and resulted in the regulation of adipogenesis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The compounds of HPLC fractions and white adipose tissue were assessed using a LC-MS system as previously described[ 21 , 25 ]. Briefly, each HPLC fraction was dissolved in 1mL of extraction solvent (99.5% EtOH).…”
Section: Methodsmentioning
confidence: 99%
“…These interesting effects of tomato consumption have been elucidated, but the active compounds in tomato are not fully understood. In recent years, we demonstrated that tomato contained fatty acid derivatives (oxylipin) that activated lipid metabolism via peroxisome proliferator-activated receptor (PPAR) α activation[ 19 21 ], which is important for fatty acid oxidation[ 22 24 ]. Although the effect of compounds in tomato on lipid metabolism has been elucidated, little is known about the effect on glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, the expression levels of the Cyp4a subfamily including Cyp4a10, Cyp4a12, and Cyp4a14 are upregulated by PPARα activation . Because PUFAs, polyphenols, and carotenoids are all potent PPARα ligands, expression levels of Cyp4a subfamily members might be regulated by dietary components which in turn control the production of 17( S ),18( R )‐EpETE and 17( R ),18( S )‐EpETE . These findings indicate that the efficacy of dietary ω3 PUFA can be regulated by various food components through the induction of CYP expression, followed by production of 17,18‐EpETE.…”
Section: Discussionmentioning
confidence: 96%